Analysis and Evaluation of Internal Control Accounting Information System on Cash Receipts and Cash Disbursements at LPD Desa Adat Jadi - I G A A Dina Purnama D; I K Parnata; I W Purwanta Suta (Jurusan Akuntansi Politeknik Negeri Bali, 2019)
This study aims to evaluate internal control over the accounting information system for cash receipts and cash disbursements at LPD Desa Adat Jadi. The results of this study are expected to provide constructive advice in improving the application of internal controls that can minimize the potential fraud and misappropriation of LPD Desa Adat Jadi’s assets. This type of research is a case study using two types of data namely primary and secondary data. Data collection techniques used were interviews, observation and documentation. The analytical technique used is descriptive analysis techniques that is by explaining the accounting information systems for cash receipts and cash disbursements and descriptive comparative analysis through a comparison of the application of internal control information systems to cash receipts and cash disbursements of LPD Desa Adat Jadi with the theory of internal control according to COSO. The results of the study show that the cash receipts and cash disbursements systems each have three activities derived from voluntary savings, time deposits and monthly loans. The results of evaluating the implementation of internal accounting information systems at LPD Desa Adat Jadi, so that they are not fully compliant with the five components of COSO internal control, only information and communication components are in accordance with COSO theory. The four components that are not in accordance with COSO are internal environment, risk assessment and risk response, control activities, and monitoring.